Loyal subjects : bonds of nation, race, and allegiance in nineteenth-century America - Duquette, Elizabeth, 1963- (Rutgers University Press, 2010)
When one nation becomes two, or when two nations become one, what does national affiliation mean or require? Loyal Subjects answers this question by demonstrating how loyalty was used during the U.S. Civil War to define proper allegiance to the Union. Through an analysis of literary works written during and after the conflict, Elizabeth Duquette reveals that although American literary criticism has tended to dismiss the Civil War's impact, postwar literature was profoundly shaped by loyalty.